Proposed long period transition map for new Indonesia earthquake resistant building code based on Indonesia seismic hazard map 2010 - Usama Juniansyah Fauzi; Achmad Fauzi; Masyhur Irsyam; F. X. Toha; . Hendriyawan (Syiah Kuala University, 2011)
The new method for determining ground-motion parameters in the next edition of the Indonesian Earthquake Resistant Building Code SNI 03-1726-X, which will be issued in this year, has significant changes than the old code. The major changes in SNI 03-1726-X are using Risk-Targeted Maximum Considered Earthquake (MCER) Spectral Response Acceleration maps. These maps developed by Team for Revision of Seismic Hazard Maps of Indonesia were based on probabilistic approach for 2% probability of exceedance in 50 years and deterministic approach by using three-dimensional seismic source models and by considering latest geological and seismological data and fragility curve of buildings. For building design, it has been decided that ASCE 7-10 will be adopted for coming code SNI 03-1725-X. The design philosophy adopted from ASCE 07-10 standard contains a significant addition consisting of a constant-displacement segment of the design response spectrum. This paper presents the proposed parameter TL developed by the author and Disaster Mitigation Research Center ITB (Pusat Penelitian Mitigasi Bencana ITB) to provide more realistic estimates of the ground motions at periods T 4 sec by consisting a constant-displacement segment.